Effect of elevated temperature irradiation on bipolar devices for space application. Issue 3 (3rd April 2019) - Pershenkov, Viacheslav S.; Telets, Vitaliy A.; Bakerenkov, Alexander S.; Rodin, Alexander S.; Felitsyn, Vladislav A.; Belyakov, Vladimir V.
ABSTRACT: The application of elevated temperature irradiation for simulating of low dose rate degradation in bipolar devices was considered. The analysis was performed in the framework of the conversion model, which enables to estimate the radiation degradation at any dose rate, temperature and total dose numerically. The possibility of application of the conversion model for the numerical estimation of radiation-induced increase of LM111 input current under low dose rate radiation impact was demonstrated experimentally. A test method using four-stage elevated single temperature irradiation was proposed. The ability of temperature-switching approach for simulation of enhanced low-dose-rate sensitivity was estimated and discussed.